Optimization of vocational education learning in pandemic times with a modified blended learning system and appropriate technology - Djubir R. E. Kembuan,; Johan R. Batmetan,; Metsi Daud,; Billy MH Kilis, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The blended/hybrid learning system is a way that can be done today with adjustments to the conventional side with the application of health protocols. Utilizing and optimizing hybrid learning by modifying and utilizing appropriate technology will provide learning solutions during a pandemic. Hybrid learning does not have to be a monopoly and ignores conventional learning. Conventional learning must also be modified according to the protocol carefully so that it remains effective. The use of appropriate technology also needs to be specifically encouraged for teachers. ICT is a shared hope, although it is undeniable that for vocational training there must be hands-on practice and training. To optimize learning with various approaches, it must still lead to effectiveness, efficiency and relevance to the object of students. Learning in vocational education has characteristics that need to be studied in more detail so that quality is maintained. In this study, the choice of surveys on students for learning options with blended learning, with a comparison of 60% conventional and 40% ICT/Online, Appropriate Technology, and combinations obtained an average result of 22.5%, 17.75%, 13 .5 % and 6.25%, (a survey of students, students, teachers and lecturers for the even semester of 2020/2021) within the scope of Unima and its surroundings. The results of a survey of students, both students, students or teachers and lecturers show that there is no full readiness in choosing various alternatives, software and hardware readiness is still needed for students and teachers in particular so that the implementation of education can be more varied in choosing alternatives and achieving the desired goals. The conclusions of this study are: Online or blended learning cannot be applied optimally in Vocational High Schools / Vocational Schools, besides the reason that it still needs face-to-face practice and training, the infrastructure is still not supported. The results of the survey on student lecturers as a comparison are generally still constrained by many things, including facilities and human resources. On the other hand, in vocational education learning the whole process must consider practice or training which means there must be limited face-to-face or group meetings. Optimizing conventional learning according to the process and blended learning must pay attention to the readiness of students including the learning environment, namely external factors and students' mental readiness, internal. For optimization so that the quality of learning is not neglected, it is necessary to consider the existence of practice and training in subjects related to practice or which require training. Some suggestions are: There is a need for the role of the government, and education stakeholders if learning is still in a pandemic period. For students and teachers, it is necessary to have adequate support facilities. Various learnings can be done if there is an equitable fulfilment of educational infrastructure. Practice facilities in SMK need to be expanded so that the groups are getting smaller and reaching more students. The practicum package needs to be made simpler with adjustments according to the process. Keywords: Optimizing Learning during the Pandemic.